Institutional communication at Spanish public universities from the approach of participatory communication - Esther Simancas González; Marcial García López (Arizona State University, 2019)
The theory and practice of institutional communication at public universities in Spain have a strong corporate and instrumental character. In this study, we discuss the possibility of implementing acommunicative planning and management focused on prioritizing more horizontal and participative communication processes. For that purpose, a qualitive study was carried out with a Delphi panel of 10 researchers from Spanish public universities specialized in participatory communication and communication for social change.The study suggests that the implementationof participative university institutional communication would require the conviction and involvement of the entire university community. It would lead to the establishment of procedures and mechanisms that guarantee the transversality of communication, as well as the active presence of different intra- and extra-university groups in the diagnosis, design, execution, and evaluation of institutional communication.